Upaya Penegakan Hukum Terhadap Pelaku Penyalahgunaan Narkotika oleh Anak - Sindy Ramadhani (Pusat Riset dan Inovasi Nasional, 2024)
Narcotics, psychotropics, and other addictive substances are a major threat to Indonesian society. According to the National Narcotics Agency (BNN), drugs can disrupt social stability and damage the younger generation. Law Number 35 of 2009 concerning Narcotics and Law Number 5 of 1997 concerning Psychotropics regulate the distribution and abuse of drugs with severe sanctions, including the death penalty for large-scale drug dealers. A different legal approach is needed to address the increasing involvement of minors in drug cases. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System provides a legal framework that focuses on restorative justice, rehabilitation, and social reintegration. The national plan includes prevention, prosecution, and rehabilitation, which involves good cooperation between law enforcement and BNN. Intervention and guidance are very important in dealing with underage drug offenders to avoid stigmatization and reduce recidivism. It is important to evaluate the success of these legal actions to ensure their positive impact in creating an environment that supports rehabilitation and a better future for children.